2021
DOI: 10.1002/ece3.7413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on life‐history traits of the newly invasive fall armyworm, Spodoptera frugiperda in Southeast China

Abstract: The fall armyworm (FAW) Spodoptera frugiperda (J. E. Smith) is an economically important pest that is native to the tropical and subtropical regions of the Americas, where it is well known as a key pest of corn (Barfield et al., 1978;Garcia et al., 2018;Sparks, 1979). The FAW cannot survive the winter in temperate North America because it cannot enter a diapause. The regions in the United States in which FAW overwinters are southern Florida and southern Texas (Barfield et al., 1978;Johnson, 1987). The moth is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 54 publications
(73 reference statements)
7
16
0
Order By: Relevance
“…The developmental time of the immature stages of FAW is significantly influenced by temperature and the type of host plant [6,25,26,36,38,40]. At higher temperatures, the development period of FAW is significantly reduced [26,36,38]. In the present study, we found that increasing temperatures significantly shortened the developmental time of FAW eggs, larvae, pre-pupae, pupae, and pre-adults on each host plant, which significantly accelerated generations.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The developmental time of the immature stages of FAW is significantly influenced by temperature and the type of host plant [6,25,26,36,38,40]. At higher temperatures, the development period of FAW is significantly reduced [26,36,38]. In the present study, we found that increasing temperatures significantly shortened the developmental time of FAW eggs, larvae, pre-pupae, pupae, and pre-adults on each host plant, which significantly accelerated generations.…”
Section: Discussionsupporting
confidence: 51%
“…Optimal temperature can improve the survival rate, accelerate the development rate of immature stages, result in more generations, and enhance the probability of their establishment [2,36,37]. The survival rate of FAW larvae and pupae increases in response to increasing temperature [36,38]. However, different temperatures do not influence the percentage of emerged FAW adults [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smith) (Lepidoptera: Noctuidae)] was in the range of 26-30 ˚C, and the larval development was fastest at 30 ˚C (Du Plessis et al, 2020). Similarly, the egg, larval, and pupal development time of FAW decreased remarkably as the temperature increased from 19 to 31 ˚C (Huang et al, 2021). A model predicts that a 2 ˚C rise in average global surface temperature would increase maize yield losses by 31%, on average, owing to pest pressure, which would mean an annual loss of 62 Tg (Deutsch et al, 2018).…”
Section: Crop Sciencementioning
confidence: 99%